2004
DOI: 10.1158/0008-5472.can-04-2151
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gene Expression Patterns and Chromosomal Changes Associated with Aging

Abstract: Age is the largest single risk factor for the development of cancer in mammals. Age-associated chromosomal changes, such as aneuploidy and telomere erosion, may be vitally involved in the initial steps of tumorigenesis. However, changes in gene expression specific for increased aneuploidy with age have not yet been characterized. Here, we address these questions by using a panel of fibroblast cell lines and lymphocyte cultures from young and old age groups. Oligonucleotide microarrays were used to characterize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 58 publications
5
55
1
1
Order By: Relevance
“…This is in line with previously reported aneuploidy rates in amniocytes studied by banding methods 2 and hESC studied by metaphase CGH 24 . On the other hand, they are in contrast with the high percentages of non-clonal aneuploidy reported by studies using FISH on cultured somatic cells 3,4 and hESC 25,26 . It is likely that the use of different techniques is the cause of these discrepancies.…”
Section: Detection Of Genetic Imbalances In Single Cells By Acghcontrasting
confidence: 81%
See 3 more Smart Citations
“…This is in line with previously reported aneuploidy rates in amniocytes studied by banding methods 2 and hESC studied by metaphase CGH 24 . On the other hand, they are in contrast with the high percentages of non-clonal aneuploidy reported by studies using FISH on cultured somatic cells 3,4 and hESC 25,26 . It is likely that the use of different techniques is the cause of these discrepancies.…”
Section: Detection Of Genetic Imbalances In Single Cells By Acghcontrasting
confidence: 81%
“…Furthermore, hESC seem to undergo subtelomeric instability at a higher frequency than somatic cells. This is distinctive from the majority of previous studies that focused on analysing single cells, which lacked the resolution to detect the majority of the CNVs described here 3,4,25,26 . As these CNVs are present at very low frequencies in the culture, they also could not be detected using the straight-forward analysis of pooled DNA, as used by most studies for high-resolution screening of cell lines.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Human fibroblasts and bone marrow hMSC grown at 20% O 2 (passage 10) presented levels of aneuploidy ranging from 12 to 18%, in line with our previous results. 23,25 Analysis of aneuploidy in cultures of these cells grown for an additional 4-10 passages at 3% O 2 and 20% O 2 confirmed that growth at 3% O 2 reduces the levels of aneuploidy in other cell types of mesenchymal origin (Figure 3d). These results strongly suggest that growth of mesenchymal cells at 20% O 2 for 5-10 passages promotes aneuploidy, and we therefore propose that ROS are a principal cause of aneuploidy in hMSC.…”
Section: Resultsmentioning
confidence: 68%